Physico-chemical and immunological studies on serum glocyproteins [i.e. glycoproteins] and their diagnostic significance in neoplastic diseases - Coetzer, Theresa Helen Taillefer (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1984.